2016
DOI: 10.4103/0974-7796.176870
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of concurrent penile and spinal schwannomas

Abstract: Schwannoma of the penis is extremely rare. This is the case of a young male who presented with pain on sexual intercourse, multiple lumps on the dorsal shaft of his penis, as well as a temporal headache. He was subsequently diagnosed with schwannoma affecting both his penile region and cauda equina. This clinical finding has not been previously described in the literature. Hence, its presentation is unique to our specialty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Despite the extensive innervation of genitalia, neurilemmomas (Schwannomas) are exceedingly rare in the penis. Two recent reviews have identified 34 cases of penile schwannomas published in the English literature and this represents the 3rd characterized PS variant isolated to the penis [35].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive innervation of genitalia, neurilemmomas (Schwannomas) are exceedingly rare in the penis. Two recent reviews have identified 34 cases of penile schwannomas published in the English literature and this represents the 3rd characterized PS variant isolated to the penis [35].…”
Section: Introductionmentioning
confidence: 99%